STAT2 is a pervasive cytokine regulator due to its inhibition of STAT1 in multiple signaling pathways - Ho, Johnathan; Pelzel, Christin; Begitt, Andreas; Mee, Maureen; Elsheikha, Hany M.; Scott, David J.; Vinkemeier, Uwe (Public Library of Science, 2016)
STAT2 is the quintessential transcription factor for type 1 interferons (IFNs), where it functions as a heterodimer with STAT1. However, the human and murine STAT2-deficient phenotypes suggest important additional and currently unidentified type 1 IFN-independent activities. Here, we show that STAT2 constitutively bound to STAT1, but not STAT3, via a conserved interface. While this interaction was irrelevant for type 1 interferon signaling and STAT1 activation, it precluded the nuclear translocation specifically of STAT1 in response to IFN-γ, interleukin-6 (IL-6), and IL-27. This is explained by the dimerization between activated STAT1 and unphosphorylated STAT2, whereby the semiphosphorylated dimers adopted a conformation incapable of importin-α binding. This, in turn, substantially attenuated cardinal IFN-γ responses, including MHC expression, senescence, and antiparasitic immunity, and shifted the transcriptional output of IL-27 from STAT1 to STAT3. Our results uncover STAT2 as a pervasive cytokine regulator due to its inhibition of STAT1 in multiple signaling pathways and provide an understanding of the type 1 interferon-independent activities of this protein.